Análise de um curso de especialização em atenção básica através de narrativas de estudantes do Programa Mais Médicos - BRASIL, Gabrielle Vieira da Silva (2018)
The shortage of doctors in remote and vulnerable areas of Primary Care (PC), which is the entrance door to Brazilian health system, has led the Federal Government to implement intervention actions. It began with initiatives such as the Primary Care Professionals Enhancement Program (Provab), although it was with the creation of the More Doctors Program (PMM) that it was possible to reach the provision of doctors in adequate time to meet Brazilian municipalities demand. In this program, it is proposed professionals permanent education through the Open University of Brazilian National Health System (UNA-SUS), with teachingservice integration and the offer of enhancement and specialization courses in distance learning modality, in order to facilitate the professional training process in the health area, according to SUS guidelines and principles. In this context, this study aims to evaluate the quality of a latu sensu course on primary care considering the opinion of students participating in PMM. The study population was composed of doctors linked to PMM that were enrolled in the specialization course on Primary Healthcare offered by UNA-SUS/UFMA, in distance learning modality, from 2014 to 2015. It is a qualitative approach, based on the narratives collected through SigU Questionnaire, subsystem developed by UNA-SUS/UFMA to evaluate its courses. For narratives analysis a content analysis of thematic modality was performed, following the steps defined by Bardin (2011), resulting in the formation of seven meaning cores: 1 – Distance course; 2 – Connectivity through internet; 3 – Virtual Learning Environment; 4 – Content and didactic material; 5 – Activities; 6 – Tutor; 7 - Relation between theory and professional practice for PC strengthening. When analyzing the narratives, it was possible to observe that internet connection still figures as a problem nowadays in some areas. The course offer, even though it is a mandatory step, was highlighted by its importance for the exchange of experiences and knowledge about SUS. The didactic material was reported as dynamic and the content as updated, resulting in the course being considered of great quality. Based on these observations, it is possible to notice a positive feedback from the students about the course offered, which contributes to the follow-up and improvement of the courses offered by UNASUS/UFMA, as well as, from the perspective of permanent health education, to the strengthening of PC and improvement of Brazilian public health.